TRANSFORMASI PLASMID PTRLI DENGAN TEKNIK ELEKTROPORASI PADA ASPERGILLUS TERREUS DAN UJI STABILITAS TRANSFORMAN - hardianto, dudi; gusnidar, tutus; singgih, marlia; musadad, amir; sumaryono, wahono (Jurnal Sains dan Teknologi Indonesia, 2012)
Aspergillus terreus is a Saprophyte fungus that produces several secondary metabolites as lovastatin (anti-cholesterol drug) and itaconic acid (a polymer material). Lovastatin is one of the statin class of drugs that have efficacy as antihypercholesterolemic. Plasmid transformation is the introduction and incorporation of exogenous plasmid into cells orprotoplast. In this study, pTRLI plasmid (pTRI inserts containing lovE gene as a regulator gene in the biosynthesis of lovastatin) will be transformed by electroporation transformation. The purpose of this research is transformation of pTRLI plasmid into protoplasts of Aspergillus terreus by electroporation and obtain stable transformants. The research was initiated by isolation of pTRLI plasmid. Then pTRLI plasmid was determined purity and concentration by nanodrop. Furthermore, Protoplasts of Aspergillus terreus were isolated enzymatically by adding an enzyme which can degrade the cell wall of Aspergillus terreus which contains chitin and cellulose. PTRLI plasmid were transformed into protoplasts of Aspergillus terreus by electroporation. These transformants were grown in Czapek-Dox medium containing pyrithiamine agar and the number of transformants mg-1 of pTRLI plasmid was calculated. Transformants were selected to grow in Czapek-Dox medium containing piritiamin 1 mg l-1. The number of transformants produced 187 transformants mg-1 of PTRLI plasmid. Transformants are stable up to five generations by growing the transformants in Czapek-Dox medium agar containing piritiamin 1 mg l-1. The success of the transformation indicated by ptrA gene in transformants that can be amplified by PCR. The size of fragment DNA is 801 bp.